X-rays for medical imaging: Radiation protection, governance and ethics over 125 years. (November 2020) - Malone, Jim
Highlights: The ICRP system is mature, integrated, self-consistent and reduced staff dose limits by a factor of 30–50 over the years. The International Congress of Radiology influence on the culture and governance of ICRP is profound and still lives on. ICRP recommendations strongly support protection of workers and the public, with less emphasis on patients. The ICRP approach to recommendations on medical exposures is often hands-off, e.g. with justification or pregnancy. The social sciences and humanities have been notably absent from the commission membership and its programme of work. Abstract: Starting from Röntgen's discovery and the first radiograph of his wife's hand, the curtain was raised on a new technique with remarkable possibilities for contributing to human health. While growth in applications proceeded rapidly, it was accompanied by significant harms to those involved and by inappropriate opportunistic application. This paper places the attempts to deal with the harms and inappropriate activities side by side with the positive developments. It attempts a narrative on the development of medical radiation protection over the 125-year period and places it in the context of a commentary on governance and ethics. The substance of the narrative is based on the recommendations of ICRP as they developed and altered over time. The governance commentary is based on assessing the independence of ICRP and its attention to medical exposures. In terms of ethics, the recommendations at each stage are reviewed in the light of values that are deemed appropriate to both medical ethics and radiation protection. The paper, while celebrating Röntgen-125, also hopefully provides a perspective for discussion as ICRP's centenary in 2028 approaches. This is an important part of ensuring continued acceptance and confident use of X-Rays, and helps underwrite the possibility of further developments in the area.